Heat‐related deaths among construction workers in the United States. Issue 12 (22nd July 2019) - Dong, Xiuwen Sue; West, Gavin H.; Holloway‐Beth, Alfreda; Wang, Xuanwen; Sokas, Rosemary K.
Abstract: Background: Heat is a severe hazard for construction workers and may be worsening with global warming. This study sought to explore heat‐related deaths among U.S. construction workers and a possible association with climate change. Methods: Heat‐related deaths in the Census of Fatal Occupational Injuries from 1992 to 2016 were analyzed. Denominators estimated from the Current Population Survey were matched with demographic and occupational categories in rate calculations. Statistical tests were used to examine heat‐related deaths in relation to time, geographic region, and temperature. Results: Construction workers, comprising 6% of the total workforce, accounted for 36% ( n = 285) of all occupational heat‐related deaths from 1992 to 2016 in the U.S. Mean temperatures from June to August increased gradually over the study period. Increasing summer temperatures from 1997 to 2016 were associated with higher heat‐related death rates ( r = 0.649; 95% confidence interval: 0.290, 0.848). Compared to all construction workers (risk index = 1), statistically significant elevated risk of heat‐related death was found among Hispanics (1.21), in particular workers born in Mexico (1.91). Occupations with a high risk index included cement masons (10.80), roofers (6.93), helpers (6.87), brick masons (3.33), construction laborers (1.93) and heating, air conditioning, and refrigeration mechanics (1.60). Conclusions: U.S. construction workers are at a high risk of heat‐related death, and this risk has increased with climate change over time. Effective workplace interventions, enhanced surveillance, and improved regulations and enforcement should accompany broader efforts to combat global warming. The construction industry can help reduce global warming through increased implementation of green building principles.